Sexuality in Poems by Shinta Febrianty: A Discourse Analysis Study - Akmal Jaya; Nurhadi Hamka; La Ode Achmad Suherman (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research delves into the feminist discourse on sexuality in Shinta Febrianty's poetry, specifically focusing on her collection, "Aku Bukan Masa Depan (2003)." Drawing on Michel Foucault's theory of Discourse and Power Relations, the study employs a qualitative approach that integrates content and discourse analysis. Through meticulous examination of Febrianty's poems, the research unpacks the intricate dynamics of power that suppress female sexuality within Indonesian literary traditions. Thematic analysis illuminates the multifaceted interplay of identity, resistance, and societal expectations embedded within Febrianty's verses. The study concludes by reflecting on the evolving landscape of Indonesian literature, particularly in light of the increasing prevalence of sexuality discourses in female-authored works. It critically questions the motives and sustainability of this trend, emphasizing the need for discerning steps to navigate the shifting cultural dynamics influenced by both local and global forces.